2022
DOI: 10.3389/fcell.2022.839986
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of KCNK Genes and Establishment of a Specific Prognostic Signature for Breast Cancer

Abstract: Two-pore domains potassium channel subunits, encoded by KCNK genes, play vital roles in breast cancer progression. However, the characteristics of most KCNK genes in breast cancer has yet to be clarified. In this study, we comprehensively analyzed the expression, alteration, prognosis, and biological functions of various KCNKs in breast cancer. The expression of KCNK1/4/6/9/10/13 were significantly upregulated, while KCNK2/3/5/7/17 were downregulated in breast cancer tissues compared to normal mammary tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In this study, we found that HECEGs of KCNK1 were mainly involved in the cell cycle pathway, and KCNK1 was closely related to the transmembrane transport of potassium ions. Previous studies have reported that, as an important gene encoding a potassium channel subunit protein, KCNK1 could control ion channels to participate in a variety of cellular activities [ 35 , 36 ]. Ion channels could promote the deterioration of cancer cells and then accelerate malignant cell proliferation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that HECEGs of KCNK1 were mainly involved in the cell cycle pathway, and KCNK1 was closely related to the transmembrane transport of potassium ions. Previous studies have reported that, as an important gene encoding a potassium channel subunit protein, KCNK1 could control ion channels to participate in a variety of cellular activities [ 35 , 36 ]. Ion channels could promote the deterioration of cancer cells and then accelerate malignant cell proliferation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of KCNN4 is associated with disease-free survival, immune infiltration, and several other clinicopathological features and can serve as a diagnostic and prognostic biomarker in TC ( 86 ). Abnormal expression of the KCNK gene family in BC can be used as an ideal prognostic biomarker for BC patients ( 118 ). It is also a powerful indicator of pan-cancer prognosis ( 115 ).…”
Section: Discussionmentioning
confidence: 99%
“…High LAMC2 expression in pancreatic cancer defines a highly metastatic stem cell subset with a reduced survival probability (Yang et al, 2020). Similarly, the potassium channel protein KCNK1, which has a two-hole domain (K2P), is dramatically increased in breast cancer tissues and is linked to a poor prognosis (Zou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%